2013
DOI: 10.1007/s00405-013-2765-9
|View full text |Cite
|
Sign up to set email alerts
|

Transient evoked otoacoustic emissions and vestibular evoked myogenic potentials in cigarette and water pipe smokers

Abstract: This study compared the amplitude of transient evoked otoacoustic emissions (TEOAEs) and latencies of vestibular evoked myogenic potentials (VEMPs) among non-smokers, cigarette smokers, water pipe smokers, mixed smokers and ex-smokers. A total of 50 non-smokers, 28 water pipe smokers, 34 pure cigarette smokers, 28 mixed cigarette-water pipe smokers, and 21 ex-smokers were evaluated in this study. Their age ranged from 20 to 40 years. All had normal hearing sensitivity and normal middle ear functions. TEOAEs am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…This may be further explained by confounding variables included in statistical models. For example, Spankovich & Le Prell (2013;2014) found tobacco smoking was related to hearing status when adjusting for similar variables to the current study, however, the relationship was no longer statistically significant when dietary quality was added to the model. Some longitudinal examinations suggest significant relationships between tobacco smoking and prevalent, but not incident, hearing loss (Karlsmose et al 2000;Gopinath et al 2010;Rigters et al 2018).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…This may be further explained by confounding variables included in statistical models. For example, Spankovich & Le Prell (2013;2014) found tobacco smoking was related to hearing status when adjusting for similar variables to the current study, however, the relationship was no longer statistically significant when dietary quality was added to the model. Some longitudinal examinations suggest significant relationships between tobacco smoking and prevalent, but not incident, hearing loss (Karlsmose et al 2000;Gopinath et al 2010;Rigters et al 2018).…”
Section: Discussioncontrasting
confidence: 41%
“…Tobacco smokers also exhibit increased levels of C-reactive protein (Tracy et al 1997; Ohsawa et al 2005), a systemic inflammatory biomarker that has been associated with incident hearing loss (Nash et al 2014). Numerous otoacoustic emission studies describe impaired cochlear function in cigarette smokers (e.g., Mustafa 2014) but few studies have been conducted to assay cochlear health in cannabis smokers. We previously reported subtle cochleopathology in young (18- to 29-year-old) cannabis smokers (Brumbach et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Paschoal and Azevedo [ 13 ], a decrease in TEOAEs was found at 1 kHz, similar to the present study. Decreases in TEOAE amplitudes have been found in smokers compared with nonsmokers in some other studies [ 14 15 ]; however, in these cases only the overall response was taken into account, without analysis of frequency bands.…”
Section: Discussionmentioning
confidence: 99%
“…Among smokers there were more cases of tinnitus. Also in the studies of Vinay [ 14 ] and Mustafa [ 15 ], overall TEOAE amplitude was significantly reduced in smokers compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have investigated whether nicotine affects hearing in humans. In human population-based studies, current smoking [ 11 ], passive smoking [ 28 ] or past smoking [ 29 ] were all reported to be associated with hearing impairment after controlling for potential confounders. In addition, Durante et al [ 15 ] reported that maternal tobacco exposure induced a significant decrease in transient evoked otoacoustic emissions amplitudes, suggesting an impact on outer hair cells.…”
Section: Discussionmentioning
confidence: 99%